2008
DOI: 10.1124/mol.108.045419
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin 13 Increases Contractility of Murine Tracheal Smooth Muscle by a Phosphoinositide 3-kinase p110δ-Dependent Mechanism

Abstract: The Th2 cytokine interleukin (IL) 13 can elicit a number of responses consistent with a key role in the pathogenesis of asthma. We have used pharmacological and genetic approaches to demonstrate the role of signaling via the class I phosphoinositide 3-kinase p110␦ isoform in IL-13-induced hyper-responsiveness of murine tracheal smooth muscle contractility in vitro. IL-13 treatment of tracheal tissue is associated with an early activation of phosphoinositide 3-kinase (PI3K), as assessed by phosphorylation of Ak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
25
1

Year Published

2008
2008
2013
2013

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 41 publications
(53 reference statements)
3
25
1
Order By: Relevance
“…More recently, p110δ PI3K has been shown to mediate IL-13-induced mouse tracheal smooth muscle hyperreactivity to methacholine [57]. We report here that artesunate significantly inhibited OVA-induced AHR to increasing concentrations of methacholine.…”
Section: Discussionsupporting
confidence: 48%
“…More recently, p110δ PI3K has been shown to mediate IL-13-induced mouse tracheal smooth muscle hyperreactivity to methacholine [57]. We report here that artesunate significantly inhibited OVA-induced AHR to increasing concentrations of methacholine.…”
Section: Discussionsupporting
confidence: 48%
“…We lastly investigated the role of phosphoinositide 3-kinases (PI3Ks), which were previously shown to regulate calcium flux in airway smooth muscle cells [30] and to be involved in the IL-13-induced increase in tracheal contractility in mouse [31]. Wortmanin (0.5 μM) and PI-828 (2 μM overnight) potentiated the relaxation to chloroquine and phenanthroline (Figure 8), which translated into a significant increase in pD 2 for relaxation to chloroquine in bronchi treated with PI-828 only (4.5 ± 0.2 in the absence of PI-828 vs .…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, we showed that LY294002 also prevents the release of IL-6 in response to TGF-β, demonstrating for the first time the involvement of PI3Ks in TGF-β-induced IL-6 release. LY294002 was effective at 5 and 10 μM, concentrations shown to potently inhibit PI3K activity in human ASMCs (17). It is possible that Smad3 and PI3K may act synergistically to induce Nox4 expression and IL-6 release.…”
Section: Discussionmentioning
confidence: 99%